PKM PENINGKATAN KETRAMPILAN LITERASI DIGITAL PEMUDA KARANG TARUNA DESA PULUTAN KECAMATAN REMBOKEN KABUPATEN MINAHASA - Cynthia Maria Siwi; Obed Bida (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
A youth group in Pulutan Village, Minahasa Regency, benefited from mentoring and training to improve their digital literacy skills as part of a community service project. The inability of Pulutan village youth to run digital applications is the driving force behind these instructions. In addition, untrue news can be detrimental to society, which is very easy for individuals to digest because of the widespread spread of HOAX among teenagers. The objectives of this PKM include the following: 1) encouraging youth to be more proficient in using applications through multimedia training 2) educating the public about how to use digital literacy to filter information circulating in society; 3) offer opportunities and work experience to lecturers and students; and 4) encourage collaboration with various related parties, especially youth organizations to promote Manado Open University to the wider community. Lectures and training are the means to achieve the objectives of this PKM. Lectures and group discussions are used to present training-related materials. After that, more direct instructions were carried out with hands-on experience. Overall, the results of the PKM activities were positive and satisfying. One of the elements that was successfully carried out effectively in this activity was the achievement of the activity objectives, and the other element was the achievement of the intended material objectives